Seizure after surgical treatment of chronic subdural hematoma—Associated factors and effect on outcome - Hamou, Hussam; Alzaiyani, Mohammed; Rossmann, Tobias; Pjontek, Rastislav; Kremer, Benedikt; Zaytoun, Hasan; Ridwan, Hani; Clusmann, Hans; Hoellig, Anke; Veldeman, Michael (Frontiers in Neurology, 2022)
Introduction Chronic subdural hematoma (cSDH) is becoming more prevalent due to population aging and the increasing use of antithrombotic drugs. Postoperative seizure in cSDH have a negative effect on outcome, and there currently no consensus regarding prophylactic anti-epileptic drug (AED) treatment. The objective of this study was to evaluate predisposing and triggering factors associated with postoperative epileptic seizure in patients with cSDH. Methods All patients, who were surgically treated for cSDH in a single tertiary care center between 2015 and 2019, were considered for inclusion. Relevant patient- and hematoma-specific characteristics were retrospectively extracted from hospital records. Paroxysmal events categorized by the treating physician as suspected postoperative seizures were noted. The clinical outcome was extracted from the last available follow-up visit and classified according to the Glasgow outcome scale (GOS). Results Of the included 349 patients, 54 (15.5%) developed suspected postoperative epileptic complications in the form of early seizure (≤ 7 days) in 11 patients (3.2%) and late seizure (>7 days) in 43 patients (12.3%). In the logistic regression analysis, solely depressed brain volume (supratentorial volume (ml) not filled with re-expanded brain) was independently associated with postoperative seizure (odds ratio [OR] 1.006, 95% CI: 1.001–1.011; p = 0.034). The occurrence of postoperative seizure (OR 6.210, 95% CI: 2.704–14.258; p < 0.001) and preoperative Markwalder grading (OR 2.919, 95% CI: 1.538–5.543; p = 0.001) were independently associated with unfavorable (GOS1−3) outcome. Conclusion Larger postoperative depressed brain volume was the only factor independently associated with suspected postoperative seizure, and it could help identify a subgroup of patients with higher susceptibility to epileptic events. Based on our data, no formal recommendation can be made regarding the prophylactic use of anti-epileptic drugs. Nevertheless, the relative safety of new generation AEDs and the detrimental effect of postoperative seizure on outcome may justify its use in a selected patient population.